Stomach content analysis of snakehead fish (Channa striata ,Bloch 1793) in the Sei Paku Reservoir, Kampar Kiri Sub-Regency, Kampar Regency, Riau Province - Yosep Juven Yobi F Sitanggang; Deni Efizon; Ridwan Manda Putra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTSnakehead fish (Channastriata) is one of  fish living in the SeiPaku Reservoir. Research on the stomach content analysis and feeding habits of the fish has been carried out in February-April 2019. Samplings were conducted6 times, 2 weekly.  The number of fish caught was 97. The stomach content was analyzed using  a gravimetric method and the data obtained wereused for calculating the IP value. Results shown that the type of food present in the stomach were fish, insects, plants, andnot identified debris. The main foods of the snakehead fish was fish (IP 62,72%), the complementary foods was non identified animal debris(IP 37,27%)  and there were 2 additional food, namely  insects (IP 0.001) and and plants(IP 0, 02). Based on data obtained, it can be concluded that C. striata is a carnivore fish. The water quality of the reservoir were as follows: temperature 28oC-32oC, brightness of 26.15-58 cm, pH of 6, disolved oxygen of 3-5 mg/L adn cabondioxide 5.99-7.99 mg/L. Keywords: Carnivorous fish, Preponderance Index, Gravimetric, Cork fish